Optiomalisasi Bank Sampah Melalui Pendekatan Pendidikan Islam di Desa Sukajaya Kecamatan Pamarican Kabupaten Ciamis - Maulana, Helmi; Nizar S, Aditya Muhammad; Arobiah, Dede; Mahmudah, Gina; Nurhalid, Raihana; Fajrin, Risti Aulia; Tauriah, Sani; Dirgantini, Devi Delvi; Yuliani, Erni; Rianti, Rindi (Khidmat, 2021)
The Waste Bank is a crucial endeavour that holds significant importance from the standpoint of Islamic education, with a pressing need for immediate action. This article elucidates the function of trash banks in fostering the principles of hygiene, ecological accountability, and equitable treatment in accordance with Islamic doctrines. We examine the dual benefits of waste banks, which not only aid in environmental conservation but also offer economic advantages to society. This is particularly significant for instilling environmental consciousness in the younger generation and fostering a sense of collective responsibility towards the environment. This article employs a literary technique and highlights an Islamic perspective to make a compelling case for the need of garbage banks in the context of education and sustainable development, grounded in Islamic values.